2014
DOI: 10.4028/www.scientific.net/amm.592-594.879
|View full text |Cite
|
Sign up to set email alerts
|

Improving Surface Hardness of Mild Steel Plates by Addition of Silicon Carbide Using Gas Tungsten Arc as Heat Source

Abstract: An attempt has been made to improve the surface hardness property of mild steel by developing a composite layer on the surface of mild steel using gas tungsten arc as heat source. Silicon Carbide was placed on the surface using a binder and heat was applied using gas tungsten arc. Variation of Silicon content with the weld current parameters was studied. The variation of microhardness with Silicon content on the surface was studied. Optimum parameter for attaining maximum surface hardness property using GTAW (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…However, in the present work, substantial increases in the microhardness were recorded. Initially, this result was not entirely unexpected, as previous work with lasers and TIG employing higher energy inputs than the present work but with similar volumes of SiC powder, reported SiC particles along with iron silicides, contributing to an increased hardness [26,[28][29][30][31].…”
Section: Energy Kvsupporting
confidence: 79%
See 1 more Smart Citation
“…However, in the present work, substantial increases in the microhardness were recorded. Initially, this result was not entirely unexpected, as previous work with lasers and TIG employing higher energy inputs than the present work but with similar volumes of SiC powder, reported SiC particles along with iron silicides, contributing to an increased hardness [26,[28][29][30][31].…”
Section: Energy Kvsupporting
confidence: 79%
“…More recently Buytoz [28] has undertaken TIG processing of steel, studying several different SiC contents and using a range of energy inputs, some resulting in the dissolution or partial dissolution of SiC particulates. Also Reddy et al [29] used a TIG torch shielded by argon to incorporate ∼ 50 μm size SiC into mild steel. A linear increase in hardness with Si content from that of the mild steel, 160 Hv (Si 0.23%), to ∼ 400 HV (Si 1.5%) was recorded.…”
Section: Introductionmentioning
confidence: 99%
“…The SiC dissociated, and precipitated as Fe 2 Si, raising the hardness from 190HV of the mild steel substrate to ~600HV at the surface. The incorporation of ~50µm size SiC particles into mild steel, by the use of TIG heating, undertaken by Reddy et al [17], increased the surface hardness to ~400HV. A linear increase in hardness with Si content, from the mild steel, 160Hv (Si 0.23%), to ~400HV (Si 1.5%) was recorded.…”
Section: Introductionmentioning
confidence: 99%
“…The hardness increment results from SiC reinforcing particles whose precipitation strengthens the coating layer [66]. Reddy et al [67] identified that with increasing the amount of micron size SiC as a coating material, the micro-hardness of the coated surface was increased upto 147% of as received mild steel due to dispersion hardening. A similar investigation had been done to develop a coating layer of SiC on SAE 1020 carbon steel, which enhanced microhardness value in the range of 744-1135 HV.…”
Section: Sic As Coating Materialsmentioning
confidence: 99%